How does a primary school organize outdoor swimming and water safety lessons? - Torbjørn Lundhaug; Hege Randi Eriksen (Cappelen Damm Akademisk NOASP, 2022)
The main purpose of this study was to explore how a primary school organized a week with outdoor education, and especially what characterized the outdoor swimming and water safety (SWS)-lessons. The SWS-lessons were part of the physical education (PE) program. Two teachers and one headmaster from a primary school participated in the study. Four days of video observation of SWS-lessons were used in photo-elicitation interviews with teachers and the headmaster. The findings revealed that the headmaster highly prioritized the outdoor education practice in this school and that the teachers' colleagues showed great eagerness to cooperate and prioritize these lessons. The week's organization was characterized by collaborating management, and the outdoor SWS-lessons were characterized by experiential learning, challenge by choice, and risk awareness. The outdoor education practice corresponded well with the Norwegian curriculum goals about learning to be safe in, on, and around water.